2019
DOI: 10.4049/jimmunol.1900476
|View full text |Cite
|
Sign up to set email alerts
|

High GILT Expression and an Active and Intact MHC Class II Antigen Presentation Pathway Are Associated with Improved Survival in Melanoma

Abstract: The MHC class I Ag presentation pathway in melanoma cells has a well-established role in immune-mediated destruction of tumors. However, the clinical significance of the MHC class II Ag presentation pathway in melanoma cells is less clear. In Ag-presenting cells, IFN-γ–inducible lysosomal thiol reductase (GILT) is critical for MHC class II–restricted presentation of multiple melanoma Ags. Although not expressed in benign melanocytes of nevi, GILT and MHC class II expression is induced in malignant melanocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…Notably, the low-risk group was enriched in inflammation-related gene pathways such as “inflammatory response,” “interferon-α response,” and “interferon-γ response,” which suggested that the secretion of inflammatory factors might originate from the tumor cells, indicating a strong proinflammation potential in the early tumorigenesis stage ( Figure 7A ). A similar phenomenon had been reported in melanoma, breast cancer, and colorectal cancer, where the expression of immune-related genes was also presented by tumor cells and could likely be an independent influence on their prognostic differences ( Sconocchia et al, 2014 ; Forero et al, 2016 ; Buetow et al, 2019 ; McCaw et al, 2019 ; Jin et al, 2020 ).…”
Section: Resultssupporting
confidence: 76%
“…Notably, the low-risk group was enriched in inflammation-related gene pathways such as “inflammatory response,” “interferon-α response,” and “interferon-γ response,” which suggested that the secretion of inflammatory factors might originate from the tumor cells, indicating a strong proinflammation potential in the early tumorigenesis stage ( Figure 7A ). A similar phenomenon had been reported in melanoma, breast cancer, and colorectal cancer, where the expression of immune-related genes was also presented by tumor cells and could likely be an independent influence on their prognostic differences ( Sconocchia et al, 2014 ; Forero et al, 2016 ; Buetow et al, 2019 ; McCaw et al, 2019 ; Jin et al, 2020 ).…”
Section: Resultssupporting
confidence: 76%
“…Part of the studies suggested that IFI30 acted as a tumor suppressor in some tumors. The study of Kenneth H. Buetow showed high expression of IFI30 and an active and intact class II MHC antigen presentation pathway was associated with improved melanoma survival 16 . Hannah Phipps-Yonas's study indicated that low IFI30 expression was associated with poor patient survival in diffuse large B-cell lymphoma 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have revealed that IFI30 plays an indispensable role in the immune response of malignant tumors, such as melanoma, prostate cancer and glioma [16][17][18]. However, the role of IFI30 in breast cancer is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Interferon-gamma-inducible protein 30 (IFI30), also known as gamma-interferon-inducible lysosomal thiol reductase (GILT), is involved in major histocompatibility complex (MHC) class I-restricted cross-presentation and MHC class II-restricted antigen processing pathways of adaptive immunity and constitutively expressed in most antigen-presenting cells, including B cells, bone marrowderived dendritic cells, monocytes, and macrophages (12)(13)(14). IFI30 is also expressed at increased levels in various cancers such as breast cancer and melanoma (12,15). In addition, IFI30 may be linked to disease progression in prostate cancer (16).…”
Section: Introductionmentioning
confidence: 99%